Community engagement in sexual health and uptake of HIV testing and syphilis testing among MSM in China: a cross‐sectional online survey. Issue 1 (1st January 2017) - Zhang, Tiange P.; Liu, Chuncheng; Han, Larry; Tang, Weiming; Mao, Jessica; Wong, Terrence; Zhang, Ye; Tang, Songyuan; Yang, Bin; Wei, Chongyi; Tucker, Joseph D.
Abstract: Introduction : HIV and syphilis testing rates remain low among men who have sex with men (MSM) in low‐ and middle‐income countries (LMICs). Community engagement has been increasingly used to promote HIV testing among key populations in high‐income countries, often in settings with stronger civil society. This study aimed to assess socio‐demographic, behavioural, and community engagement factors associated with HIV and syphilis testing among MSM in China. Methods : MSM ≥16 years old who had condomless sex in the past three months were recruited nationwide to complete a cross‐sectional online survey in November 2015. Data were collected on socio‐demographics, sexual behaviours, HIV testing, syphilis testing, and community engagement in sexual health. We defined community engagement in sexual health using six items assessing awareness and advocacy of sexual health programmes. The underlying factor structure of a 6‐item community engagement scale was determined through exploratory factor analysis. Univariate and multivariable logistic regressions identified correlates of HIV and syphilis testing. Results : 1189 MSM were recruited. 54% (647/1189) of men had ever tested for HIV and 30% (354/1189) had ever tested for syphilis. Factor analysis suggested three levels of community engagement (minimal, moderate, and substantial) and this model explained 79.5% of observed variance. A quarter (26%, 312/1189) reported none to minimal engagement, over one half (54%, 644/1189) reported moderate engagement, and a fifth (20%, 233/1189) reported substantial engagement. Multivariable logistic regression showed that MSM with greater community engagement in sexual health were more likely to have ever tested for HIV (substantial vs. no engagement: aOR 7.91, 95% CI 4.98–12.57) and for syphilis (substantial vs. no engagement: aOR 5.35, 95% CI 3.16–9.04). Conclusions : HIV and syphilis testing are suboptimal among MSM in China. Community engagement may be useful for promoting testing in China and should be considered in intervention development and delivery. Further research is needed to better understand the role of LMIC community engagement in HIV interventions.